2000
DOI: 10.1007/pl00008258
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 is essential for vaccine-induced protection and for resolution of primary infection in murine filariasis

Abstract: The pathways conferring immunity to human filariases are not well known, in part because human-pathogenic filariae do not complete a full life cycle in laboratory mice. We have used the only fully permissive infection of mice with filariae, i.e., infection of BALB/c mice with the rodent filarial nematode Litomosoides sigmodontis. Our previous results showed that worm development is inversely correlated with Th2 cytokine production and eosinophilia. The scope of the present study was to directly elucidate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
74
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 16 publications
5
74
1
Order By: Relevance
“…The kinetics of the recovery rate have been well defined in the L. sigmodontis mouse model; as observed in other experimental filarial systems (6), the recovery rate drops a few hours after challenge inoculation (phase 1) and then remains stable (phase 2) for 2 months (24,26,29). In BALB/c mice vaccinated with irradiated larvae, the recovery rate follows the same kinetics; however, there is a stronger reduction during phase 1, amounting to 65 to 70% protection (24,29).…”
mentioning
confidence: 64%
“…The kinetics of the recovery rate have been well defined in the L. sigmodontis mouse model; as observed in other experimental filarial systems (6), the recovery rate drops a few hours after challenge inoculation (phase 1) and then remains stable (phase 2) for 2 months (24,26,29). In BALB/c mice vaccinated with irradiated larvae, the recovery rate follows the same kinetics; however, there is a stronger reduction during phase 1, amounting to 65 to 70% protection (24,29).…”
mentioning
confidence: 64%
“…However, as suggested by studies on suckling rats (Zhang et al 2001), other pathways might occur in the digestive tract. A correlation between IL-5 production and growth (Martin et al 2000 a, b;Babayan et al 2003) had been suggested during the larval stages. Haematophagy, however, seems to be a characteristic of the adult stage and may contribute to sexual maturation and thus the fitness of L. sigmodontis with its hosts.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that L3, after transmission into the skin of mice, migrate via the lymphatics (27)(28)(29) into the pleural space. Accordingly, CCL17 expression was detected not only upon artificial stimulation of BMDCs but also in CD11 + DCs in the skin, in the draining lymph nodes and the lung after natural filarial infection.…”
Section: Discussionmentioning
confidence: 99%